2021
DOI: 10.1146/annurev-ento-041420-075608
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Chewing Lice (Phthiraptera) Infesting Birds (Aves)

Abstract: In the past 25 years, studies on interactions between chewing lice and their bird hosts have increased notably. This body of work reveals that sampling of live avian hosts, collection of the lice, and the aggregated distributions of louse infestations pose challenges for assessing louse populations. The number of lice on a bird varies among host taxa, often with host size and social system. Host preening behavior limits louse abundance, depending on bill shape. The small communities of lice (typically one–four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 108 publications
(192 reference statements)
2
6
0
Order By: Relevance
“…In almost all cases, the sex ratio of male to female lice for Manitoba thrushes was less than 1.0, regardless of whether the lice were Amblycera or Ischnocera, as often observed for chewing lice on passeriform birds (Marshall 1981;Clayton et al 1992;Galloway and Lamb 2021). The sex ratio in R. elongatus was particularly low: out of 89 adult lice collected from 570 American robins, only eight were males.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In almost all cases, the sex ratio of male to female lice for Manitoba thrushes was less than 1.0, regardless of whether the lice were Amblycera or Ischnocera, as often observed for chewing lice on passeriform birds (Marshall 1981;Clayton et al 1992;Galloway and Lamb 2021). The sex ratio in R. elongatus was particularly low: out of 89 adult lice collected from 570 American robins, only eight were males.…”
Section: Discussionmentioning
confidence: 79%
“…Louse populations show seasonal patterns of abundance on some bird species (Galloway and Lamb 2021), with the pattern more evident for mean intensity than for prevalence (Galloway and Lamb 2015). For all three species of Manitoba thrushes, American robin, Swainson's thrush, and hermit thrush, where sample size was sufficiently large, migrating birds arriving in spring carried more lice than those migrating south in autumn.…”
Section: Discussionmentioning
confidence: 99%
“…3.33±0.614 (Table 2; Figure 3). The gender-wise population was also checked to determine the reproductive capability of these lice species, as the female population is always observed higher than males and the nymphal population is higher than adults (Hamstra and Badyaev, 2009;Naz et al, 2010;Kumar et al, 2013;Ahmad et al, 2015;Begum et al, 2019;Siyal et al, 2019;Galloway and Lamb, 2021); in the present study, 137 males, 178 females and 90 nymphs were collected; the sex ratio showed the similar results, but age ratio showed the abundance of nymphs is lower than adults (Table 2). This factor may be affected by the weathering conditions, as the climate of Sindh province is normally getting more dry, warm and windy, especially near the water bodies.…”
Section: Resultsmentioning
confidence: 99%
“…The water in the lakes and rivers of Sindh become dry or has less water during most of the summer season spanning about 7 months of the year and the temperature reaches up to 45-50℃ (Khan and Gadiwala, 2013; Abbas et al, 2018;Umar et al, 2018). Hence, it is possible that due to the sandy airy parts near the rivers and lakes like River Indus, the fine particles of dust and sand can penetrate the feathers and help the birds to eliminate the lice, especially the young nymphs that have a weak grip on feathers of their hosts (Clayton et al, 2010;Grossi, 2013;Bush and Clayton, 2018;Galloway and Lamb, 2021). The effects of average humidity and temperature of the study sites were also observed (Table 3) that where the humidity was low with the rise of temperature, the abundance of the lice population was recorded relatively higher (Figures 3a and 3b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation